Xeropreservation of functionalized lipid biomarkers in hyperarid soils in the Atacama Desert. (January 2017) - Wilhelm, Mary Beth; Davila, Alfonso F.; Eigenbrode, Jennifer L.; Parenteau, Mary N.; Jahnke, Linda L.; Liu, Xiao-Lei; Summons, Roger E.; Wray, James J.; Stamos, Brian N.; O'Reilly, Shane S.; Williams, Amy
Highlights: Minimal degradation of lipid biomarkers occurs in Atacama soils due to hyperaridity. Lipids retain functional groups and unsaturated bonds over geological time periods. Excellent preservation allows paleoenvironmental and paleotaxonomic reconstruction. Hyperarid environments could preserve paleobiological information on Earth and Mars. Abstract: Our understanding of long-term organic matter preservation comes mostly from studies in aquatic systems. In contrast, taphonomic processes in extremely dry environments are relatively understudied and are poorly understood. We investigated the accumulation and preservation of lipid biomarkers in hyperarid soils in the Yungay region of the Atacama Desert. Lipids from seven soil horizons in a 2.5 m vertical profile were extracted and analyzed using GC–MS and LC–MS. Diagnostic functionalized lipids and geolipids were detected and increased in abundance and diversity with depth. Deeper clay units contain fossil organic matter (radiocarbon dead) that has been protected from rainwater since the onset of hyperaridity. We show that these clay units contain lipids in an excellent state of structural preservation with functional groups and unsaturated bonds in carbon chains. This indicates that minimal degradation of lipids has occurred in these soils since the time of their deposition between > 40, 000 and 2 million years ago. The exceptional structural preservation of biomarkers is likely due to the long-term hyperaridity that has minimized microbial and enzymatic activity, a taphonomic process we term xeropreservation (i.e., preservation by drying). The degree of biomarker preservation allowed us to reconstruct major changes in ecology in the Yungay region that reflect a shift in hydrological regime from wet to dry since the early Quaternary. Our results suggest that hyperarid environments, which comprise 7.5% of the continental landmass, could represent a rich and relatively unexplored source of paleobiological information on Earth.